The Role of Notaries in Preventing Money Laundering in Indonesia: an Analysis of Compliance and Implementation of Law No. 8 of 2010 - Dahris Siregar (Jurnal Smart Hukum (JSH), 2024)
This research explores the role of notaries in Indonesia in preventing money laundering, focusing on compliance and the implementation of Law No. 8 of 2010. Utilizing a qualitative methodology, this study examines the obligations of notaries as reporting parties, the application of the Know Your Customer (KYC) principle, and the challenges faced in practice. Data were collected through document analysis, interviews with notaries, and review of official reports. The findings reveal that while regulatory frameworks mandate notaries to identify, verify, and report suspicious transactions, practical challenges persist, including limited training, technological barriers, and ethical dilemmas regarding client confidentiality. The study also highlights the effectiveness of reporting mechanisms such as the Go-AML and GRIPS applications, as well as the need for ongoing professional development and legal protection for notaries. The research concludes that strengthening institutional support and clarifying regulatory ambiguities are critical to enhancing the notary’s preventive role in money laundering activities in Indonesia.